MAIN FORMS AND ORGANIZATION OF INDEPENDENT LESSONS (Scientific journal of the Fergana State University, 2023)
The article considers the forms of self-study, determined by the purpose and objectives. The main ones are hygienic gymnastics, exercises during school hours, self-training.